Optimisation de l'algorithme de compression d’image à base de SPECK - حميداتو, ليلى; لمادي, مريم منال (university of Eloued جامعة الوادي, 2019)
The constraint of latency is an essential factor in evaluating the performance of any compression method, and it refers to calculating the time taken by the compression and decompression of images. This constraint is more or less imposed by the application targeted by the compression (transmission or archiving). In this work we propose an optimization of the image compression algorithm SPECK " Set Partionning Embedded bloCK ". The proposed approach is characterized by its speed compared to original SPECK because it manipulates fewer coefficients than the first one . يعد تقييد الوقت عاملاً أساسياً في تقييم أداء أي طريقة ضغط ، وهو بمثابة حساب الوقت الذي يستغرقه ضغط الصور وإزالة ضغطها . يتم اللجوء الى هذا القيد حسب التطبيق الذي يستهدفه الضغط (الإرسال أو الأرشفة) . في إطار هذا العمل نقترح خوارزمية تحسين ضغط الصور . SPECK تتميز هذه الطريقة المقترحة بسرعتها مقارنةً بـ SPECK الأصلي كونها تعالج معاملات أقل من الطريقة الأولى .
مذكرة ماستر تخصص في انظمة الاتصالات
Keywords: compression, decompression, transmission, archiving, SPECK; الضغط ، إزالة الضغط ، النقل ، الأرشفة ، SPECK .